DIAGNOSTICS OF THE SUBSYSTEM OF MATERIAL STIMULATION OF EMPLOYEES AT UKRAINIAN ENTERPRISES - LUKIANOVA, Valentyna; POLOZOVA, Valentyna; MALITSKY, Roman; KHLIVNENKO, Maksym (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The theoretical and applied aspects of material stimulation of employees at different groups of enterprises in Ukraine (depending on the number of employees employed) were studied. The main emphasis was placed on the diagnostics of such components as personnel costs and labor costs in the context of changes in the volume of sales of products (goods, services). It was found that during 2015-2023, a steady increase in the volume of sales of products, personnel costs and labor costs (per 1 employee) was observed for all selected groups of enterprises. However, the volume of sales of products per 1 employee is the highest for microenterprises (number of employees up to 9 people), and the value of personnel costs and labor costs is the largest in large enterprises (number of employees 250 people and more). There was a more accelerated growth of labor costs compared to personnel costs, which is explained by the different amounts of deductions for social measures for individual groups of enterprises (the highest average level of deductions for micro-enterprises). During the studied period, there was an excess of wage growth indices over labor productivity indices for all groups of enterprises (with a small number of point exceptions, first of all in 2016). The gap in the growth of product sales volumes and labor costs is increasing for medium-sized and large enterprises (the number of employees is 50 or more). The greatest lag is observed for large enterprises along with the largest values of personnel costs and labor costs, in particular. This allows us to conclude that intangible incentives are present and growing in importance for small and micro-enterprises. Employee motivation systems require constant attention and improvement both in the context of the effectiveness of tangible and intangible incentives.